The acceptance of zinc biofortified rice in Latin America: A consumer sensory study and grain quality characterization - Woods, Bo-Jane; Gallego-Castillo, Sonia; Talsma, Elise F.; Álvarez, Daniel (Public Library of Science, 2020)
Zinc deficiency is a major public health problem in vulnerable populations of Latin America and the Caribbean. Biofortification of rice (*Oryza sativa* L.) with zinc has the potential to alleviate zinc deficiencies. However, as plant breeding processes can alter grain culinary quality and favorable sensory attributes, grain quality and consumer acceptability need to be assessed prior to releasing a variety to the public. A grain quality characterization and a sensory acceptability analysis were carried out with two varieties of zinc biofortified rice and a local control both in Bolivia and Colombia. The aim of this study was to evaluate the physicochemical parameters that are significant in consumer acceptance and to determine the acceptability of zinc biofortified rice by consumers. Results of physicochemical parameters were analyzed using ANOVA. The sensory acceptability was evaluated in 243 adults utilizing a 7-point hedonic scale and a Wilcoxon's signed rank test was used to determine the overall acceptability of the varieties. Biofortified rice variety T2-11 and MAC-18 -control 1- were equally accepted by consumers in Bolivia with no significant differences (p<0.05). The grain quality analysis reported that both presented long and slender rice grains (L>7.5 mm and L/B>3), an intermediate to high amylose content (>25%) and a similar level of chalkiness. In Colombia, the biofortified variety 035 presented a higher score in overall acceptance in comparison to biofortified variety 021 and the local variety CICA4 -control 2-. However, no significant differences were observed (p<0.05). Conversely to the other two varieties, the biofortified variety 035 presented the largest size grain (L/B = 2.97), a lower chalkiness and an amylose content above 25%. This study shows that the grain quality properties of rice have an influence on acceptability and that zinc biofortified rice varieties are accepted by consumers.